Efficiency of LED lamps used in cereal crop breeding greenhouse - Stefański, Piotr; Siedlarz-Słowacka, Patrycja; Matysik, Przemysław; Rybka, Krystyna (International Journal of Agricultural and Biological Engineering, 2022)
LED lamps, which are becoming prevalent in horticulture, are also being installed in greenhouses dedicated to cereal crop breeding. However, the issue arises with the real efficiency of LED lamps. Besides high-budget programs, the smaller breeding companies in Poland face problems concerning the plant growth under LED lamps and the real costs of their exploitation. The experiment was conducted to compare seven different LED lamps and a high-intensity discharge (HID) lamp with a high-pressure sodium lamp (HPS) used as a control. For studies, two varieties of wheat, barley, and oat species were used. The plants’ growth rate was assessed based on elongation growth and earing time. Plants’ physiological conditions were evaluated using chlorophyll a (Chl a) fluorescence measured on dark-adapted leaves. The light spectra and intensities of tested lamps in parallel with electricity consumption were also recorded. The results showed that 1) LEDs’ physical properties and luminaire construction influence the amount of electricity consumed; 2) the cereal crop species differ in lighting requirements. The less light-sensitive was oat opposite barley, with wheat of moderate sensitivity; 3) LED-6 lamp (PlantaLux S.A, Lublin, Poland) based on white diodes enriched by blue ones was the most cost-efficient and most optimal for studied species. Keywords: greenhouse, light-emitting diodes, cost-effectiveness, cereal, Triticum aestivum, Hordeum vulgare, Avena sativa DOI: 10.25165/j.ijabe.20221502.5775 Citation: Stefański P, Siedlarz-Slowacka P, Matysik P, Rybka K. Efficiency of LED Lamps used in cereal crop breeding greenhouse. Int J Agric & Biol Eng, 2022; 15(2): 75–83.